Battery cell, battery device, and electric device, method for manufacturing battery cell
Patent Information
- Application Number
- CN202510423978.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,目前固态电池单体的循环性能仍较差
[0018] The ion change rate of composite halides in humid air environments is within the above range, and they have good stability. On the one hand, this can improve the overall stability of the positive electrode sheet and the cycle performance of the battery cell. On the other hand, it can reduce the stringent requirements for environmental humidity during battery assembly, reduce the construction cost of the workshop, and reduce the production cost.
Smart Images

Figure CN122931053A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of batteries, and in particular to a battery cell, a battery device, an electrical device, and a method for preparing the battery cell. Background Technology
[0002] Compared to battery cells that use liquid electrolytes, solid-state battery cells use solid electrolyte materials, which makes them less prone to combustion and explosion, and thus have high reliability and high energy density.
[0003] However, the cycle performance of solid-state battery cells is still relatively poor. Summary of the Invention
[0004] This disclosure provides a battery cell, a battery device, an electrical device, and a method for preparing a battery cell, which can improve the cycle performance of the battery cell.
[0005] In a first aspect, this disclosure provides a battery cell including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer including a composite halide electrolyte and a positive electrode active material.
[0006] The composite halide electrolyte includes halide electrolyte particles and an ion-conducting-insulating composite layer. The ion-conducting-insulating composite layer covers at least a portion of the surface of the halide electrolyte particles. The ion-conducting-insulating composite layer includes an oxide, and the oxide includes a first non-lithium cation. The halide electrolyte particles include a second non-lithium cation, and the first non-lithium cation is selected from at least one of the second non-lithium cations.
[0007] The composite halide electrolyte in the positive electrode includes a core halide electrolyte and an ion-conducting-insulating composite layer that covers at least part of the core surface. The core halide electrolyte has good ionic conductivity and high oxidation potential stability. The ion-conducting-insulating composite layer is an oxide material containing MO (transition metal-oxygen) bonds after the core halide electrolyte is oxidized. It not only has good ion-conducting ability, but also has high MO bond energy and good chemical stability. It can hinder the attack of H2O on the electrolyte crystal structure, reduce the side reactions of Li-X and TM-X bonds with water, improve the stability of the composite halide in humid air environment, and improve the cycle performance of solid-state battery cells.
[0008] In some implementations, the first non-lithium cation and the second non-lithium cation are of the same type.
[0009] Therefore, with the first and second non-lithium cations being of the same type, the ion-conducting-insulating composite layer exhibits better compatibility with the halide electrolyte particles at the interface. This allows the ion-conducting-insulating composite layer to more tightly and uniformly cover the surface of the halide electrolyte particles, reducing interface defects and gaps. This favorable bonding facilitates ion conduction between the two, reducing interfacial resistance and thus improving the overall ion conduction efficiency of the composite halide electrolyte. This provides a smoother ion transport channel for the battery cell, increasing discharge capacity and initial efficiency. Simultaneously, the identical type of the first and second non-lithium cations reduces performance fluctuations caused by compositional differences between the halide electrolyte particles and the surface ion-conducting-insulating composite layer, contributing to the stability and consistency of battery performance during multiple cycles and improving the cycle performance of solid-state battery cells.
[0010] In some implementations, the thickness of the ion-conducting-insulating composite layer is 5 nm to 20 nm.
[0011] Within the aforementioned range, the thickness of the ion-conducting-insulating composite layer not only improves the structural stability of the composite halide in humid air environments, suppresses electrolyte / cathode interface reactions, and enhances cycle performance, but also ensures that the composite halide electrolyte has high ionic conductivity and good lithium-ion transport kinetics. This allows the battery cell to have both good cycle performance and high discharge capacity, thus balancing capacity and cycle life.
[0012] In some embodiments, the halide electrolyte particles comprise Li x M 1a M 2b X c The material, wherein the second non-lithium cation includes cations corresponding to elements M1 and M2, M1 includes one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy, M2 includes one or more of Si, Ge, Sn, Ti, Zr, and Hf, and X includes one or more of F, Cl, Br, and I, 1≤x≤3.2, 0≤a≤1, 0≤b≤1, 3≤c≤7, and 0.9≤a+b≤1.1.
[0013] The aforementioned halide electrolytes have a wide voltage window and exhibit good electrochemical stability at high voltages.
[0014] In some embodiments, the halide electrolyte particles include Li 2.4 Y 0.4 Zr 0.65 Cl 6.2 Li 2.5 La 0.5 Zr 0.5 Cl6, Li 2.4 La0.43 Zr 0.5 Cl 6.1 One or more of them.
[0015] In some embodiments, the oxide includes a first material and a second material, wherein the first material includes a material with the molecular formula Li. x1 N 1a1 O n1 The material Z1c1, the second material includes N... 2a2 O n2 The material Z2c2; wherein, the first non-lithium cation includes cations corresponding to elements N1 and N2, N1 and N2 each independently include one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, Dy, Si, Ge, Sn, Ti, Zr, and Hf, and Z1 and Z2 each independently include one or more of F, Cl, Br, and I; 0.5≤x1≤1, 0.5≤a1≤1, 1≤n1≤5, 0≤c1≤4, 0.5≤a2≤1, 1≤n2≤5, and 0≤c2≤4.
[0016] The oxide material of the ion-conducting-insulating composite layer is, as mentioned above, a mixture of at least lithium-containing oxyhalides and lithium-free oxyhalides. Both contain MO (transition metal-oxygen) bonds, which can reduce side reactions between Li-X and TM-X bonds and water, improving the humid air environment of the composite halide electrolyte. The lithium-containing oxyhalide first material has good ion-conducting properties, improving the capacity performance of the battery cell, and can capture O2 generated by the decomposition of the positive electrode active material in the positive electrode film layer through Li+ vacancies. 2 - It suppresses oxygen release and does not contain lithium oxyhalides. The second material has halogen ion vacancies that form composite defects with the Li+ vacancies of the first material. Through electron transfer, it can enhance the electron-ion coupling at the interface and improve the structural stability of the composite halide in the positive electrode. As a result, the battery cell has good charge and discharge capacity and first efficiency, as well as good cycle performance.
[0017] In some embodiments, the composite halide electrolyte satisfies: (σ1-σ2) / σ1 is 0.1 to 0.3; σ1 is the ionic conductivity of the composite halide electrolyte in an environment of 30°C, and σ2 is the ionic conductivity of the composite halide electrolyte after standing in an environment of -50°C for 12 hours.
[0018] The ion change rate of composite halides in humid air environments is within the above range, and they have good stability. On the one hand, this can improve the overall stability of the positive electrode sheet and the cycle performance of the battery cell. On the other hand, it can reduce the stringent requirements for environmental humidity during battery assembly, reduce the construction cost of the workshop, and reduce the production cost.
[0019] In some implementations, σ2 is 0.9 mS / cm to 1.3 mS / cm.
[0020] The composite halide electrolyte exhibits good ionic conductivity and stability after prolonged exposure to humid air.
[0021] In some implementations, σ1 is 0.7 mS / cm to 3 mS / cm.
[0022] Composite halide electrolytes with an ion-conducting-insulating composite layer on their surface not only have a small ion change rate in humid air environments, but also maintain good ion conductivity at 30°C, which is beneficial for improving discharge capacity and first-time efficiency. They can have good lithium-ion transport capabilities while improving stability in humid air environments, thus taking into account both the cycle performance and capacity performance of individual battery cells.
[0023] In some embodiments, the mass fraction of the composite halide electrolyte in the positive electrode film is 10% to 40%.
[0024] Within the aforementioned range, the mass fraction of the composite halide electrolyte in the positive electrode film can be balanced with the content of the positive electrode active material in the positive electrode sheet, thereby achieving good ionic conductivity in the positive electrode film while maintaining high energy density in the battery cell.
[0025] In some embodiments, the volume distribution particle size Dv50 of the composite halide electrolyte is 1 μm to 3 μm.
[0026] In some embodiments, the positive electrode active material includes one or more of transition metal oxides, lithium phosphates, and their respective modified compounds.
[0027] In some embodiments, the battery cell further includes a solid electrolyte layer, which comprises sulfide electrolyte particles, and the sulfide electrolyte particles comprise Li 7-a PS5Cl a Li 10 GeP2S 12 One or more of Li3PS4.
[0028] Secondly, embodiments of this disclosure provide a battery device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure.
[0029] Thirdly, embodiments of this disclosure provide an electrical device comprising a plurality of battery cells according to any embodiment of the first aspect of this disclosure or a battery device according to any embodiment of the second aspect of this disclosure.
[0030] Fourthly, embodiments of this disclosure provide a method for preparing a single battery cell, comprising:
[0031] A first halide electrolyte is provided, and the first halide electrolyte is oxidized to form an ion-conducting-insulating composite layer containing oxides on at least a portion of the surface of the first halide electrolyte, thereby preparing a composite halide electrolyte.
[0032] A positive electrode slurry is prepared by placing a composite halide electrolyte and a positive electrode active material in a solvent, and the positive electrode slurry is provided to form a positive electrode sheet on at least one side of the positive electrode current collector;
[0033] A battery cell is formed by assembling a positive electrode, a solid electrolyte layer, and a negative electrode.
[0034] The first halide electrolyte is an unoxidized electrolyte that, after oxidation, forms at least a portion of its surface with an ion-conducting-insulating composite layer containing oxides, forming a core-shell-like structure. The shell corresponds to the ion-conducting-insulating composite layer formed after oxidation, thus forming a composite halide electrolyte.
[0035] This method controls surface oxidation of the first halide electrolyte through heat treatment, enabling the construction of a controllable thickness ion-conducting-insulating composite layer containing oxides on the surface. While the composite halide electrolyte exhibits high bulk ion conductivity, the oxide material in the surface ion-conducting-insulating composite layer contains transition metal (TM)-O bonds, which reduces side reactions between Li-X, TM-X bonds, and water. This improves the electrolyte's wet air stability while maintaining good lithium-ion transport kinetics. Simultaneously, the surface ion-conducting-insulating composite layer suppresses oxygen release from the ternary cathode during cycling, thereby improving the cycle performance of the battery cells. This method is simple, controllable, and allows for thin-layer inert passivation, while also being low-cost.
[0036] In some embodiments, the oxidation treatment temperature is 150°C to 400°C.
[0037] In some embodiments, the oxidation treatment time is 0.5 h to 3 h.
[0038] Oxidation treatments, such as increasing heat treatment time and / or temperature, can enhance the oxidation degree of the electrolyte surface, thereby controlling the thickness of the ion-conducting-insulating composite layer. A thicker ion-conducting-insulating composite layer improves water stability and electrochemical stability, and also enhances the chemical compatibility between the cathode material and the electrolyte.
[0039] In some embodiments, the gas flow rate for oxidation treatment is 50 mL / min to 100 mL / min.
[0040] In some embodiments, the atmosphere for the oxidation treatment includes 0.1% to 2% O2 by volume and / or 98% to 99.9% inert gas by volume. Attached Figure Description
[0041] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0042] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of the present disclosure;
[0043] Figure 2 This is a schematic diagram of an electrical device according to one embodiment of the present disclosure;
[0044] Figure 3 This is the O1s X-ray photoelectron spectroscopy spectrum of the composite halide electrolyte of Embodiment 1 of this disclosure.
[0045] The following is an explanation of the reference numerals in the attached diagram: 5. Battery cell;
[0046] The accompanying drawings are not necessarily drawn to scale. Detailed Implementation
[0047] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery module, battery cell, battery device, and power-consuming device, as well as methods for manufacturing the battery cell. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this disclosure and are not intended to limit the subject matter of the claims.
[0048] The "range" disclosed in this disclosure is defined by a lower limit and an upper limit, whereby a given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values 1 and 2 are listed, and if maximum range values 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] Unless otherwise specified, all embodiments and optional embodiments of this disclosure can be combined to form new technical solutions.
[0050] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions.
[0051] Unless otherwise specified, all steps of this disclosure may be performed sequentially or randomly, preferably sequentially. For example, if a method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if it is mentioned that the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0052] Unless otherwise specified, in this disclosure, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.
[0053] In this disclosure, the terms "multiple" or "a variety" refer to two or more kinds.
[0054] In the description of the embodiments of this disclosure, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0055] Unless otherwise stated, the test temperature for all parameters mentioned in this disclosure is 25°C.
[0056] The battery cells mentioned in the embodiments of this disclosure are capable of charging and discharging independently. The battery cells may be cylindrical, cuboid, or other shapes, and this disclosure does not limit this. Figure 1 The example shown is a rectangular battery cell 5.
[0057] The battery cells provided in the embodiments of this disclosure may include, but are not limited to, lithium battery cells and sodium battery cells, such as lithium-ion battery cells, sodium-ion battery cells, lithium metal battery cells, sodium metal battery cells, etc. The battery cells provided in the embodiments of this disclosure include electrode assemblies.
[0058] The electrode assembly can be a wound structure or a stacked structure, and this disclosure does not limit this. The battery cell also includes an outer packaging, which can be used to encapsulate the electrode assembly. The outer packaging can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic, such as one or more of aluminum-plastic film, polypropylene, polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0059] The battery apparatus mentioned in the embodiments of this disclosure may include one or more battery cell assemblies for providing voltage and capacity. A battery cell assembly may include multiple battery cells connected in series, parallel, or mixed connections via a busbar. In some embodiments, the battery cell assembly is typically formed by arranging multiple battery cells.
[0060] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple battery cells together with cable ties.
[0061] In some embodiments, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.
[0062] As an example, the battery cell assembly can be a battery module, which can be housed in a housing by fixing the battery module in the housing.
[0063] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple battery cells to the housing.
[0064] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.
[0065] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.
[0066] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.
[0067] The technical solutions described in this disclosure are applicable to various electrical devices that use battery cells or battery devices, such as, but not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. Battery cells and battery devices are used to store or provide electrical energy.
[0068] Figure 2 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc.
[0069] Solid-state batteries possess revolutionary potential in terms of safety and energy density, making them an ideal choice for electric vehicles and energy storage systems. Halogen electrolytes, due to their excellent ionic conductivity and high oxidation potential, have become a preferred electrolyte for composite cathodes in solid-state lithium batteries. However, the MX and Li-X bonds in halide electrolytes (Li3MX6) readily undergo adsorption and hydrolysis reactions with water, leading to the production of low-ionic-conductivity byproducts such as LiCl. This limits their environmental reliability and processability in practical solid-state batteries.
[0070] In view of the above problems, this disclosure proposes a battery cell. In a first aspect, this disclosure proposes a battery cell including a positive electrode sheet. The positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a composite halide electrolyte and a positive electrode active material.
[0071] The composite halide electrolyte includes halide electrolyte particles and an ion-conducting-insulating composite layer. The ion-conducting-insulating composite layer covers at least a portion of the surface of the halide electrolyte particles. The ion-conducting-insulating composite layer includes an oxide, and the oxide includes a first non-lithium cation. The halide electrolyte particles include a second non-lithium cation, and the first non-lithium cation is selected from at least one of the second non-lithium cations.
[0072] The composite halide electrolyte in the positive electrode includes a core halide electrolyte and an ion-conducting-insulating composite layer that covers at least part of the core surface. The core halide electrolyte has good ionic conductivity and high oxidation potential stability. The ion-conducting-insulating composite layer is an oxide material containing MO (transition metal-oxygen) bonds after the core halide electrolyte is oxidized. It not only has good ion-conducting ability, but also has high MO bond energy and good chemical stability. It can hinder the attack of H2O on the electrolyte crystal structure, reduce the side reactions of Li-X and TM-X bonds with water, improve the stability of the composite halide in humid air environment, and improve the cycle performance of solid-state battery cells.
[0073] The following is a detailed explanation of this publicly disclosed proposal.
[0074] [Positive electrode plate]
[0075] In some implementations, the first non-lithium cation and the second non-lithium cation are of the same type.
[0076] Because the first and second non-lithium cations are of the same type, the ion-conducting-insulating composite layer exhibits better compatibility with the halide electrolyte particles at the interface. This allows the ion-conducting-insulating composite layer to more tightly and uniformly cover the surface of the halide electrolyte particles, reducing interface defects and gaps. This favorable bonding facilitates ion conduction between the two, reducing interfacial resistance and thus improving the overall ion conduction efficiency of the composite halide electrolyte. This provides a smoother ion transport channel for the battery cell, increasing discharge capacity and initial efficiency. Furthermore, the identical type of the first and second non-lithium cations reduces performance fluctuations caused by compositional differences between the halide electrolyte particles and the surface ion-conducting-insulating composite layer, contributing to the stability and consistency of battery performance during multiple cycles and improving the cycle performance of solid-state battery cells.
[0077] In some implementations, the thickness of the ion-conducting-insulating composite layer is 5 nm to 20 nm.
[0078] For example, the thickness of the ion-conducting-insulating composite layer can be any value or a range of any values between 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, and 20nm.
[0079] Within the aforementioned range, the thickness of the ion-conducting-insulating composite layer not only improves the structural stability of the composite halide in humid air environments, suppresses electrolyte / cathode interface reactions, and enhances cycle performance, but also ensures that the composite halide electrolyte has high ionic conductivity and good lithium-ion transport kinetics. This allows the battery cell to have both good cycle performance and high discharge capacity, thus balancing capacity and cycle life.
[0080] Further increasing the thickness of the ion-conducting-insulating composite layer will reduce the ionic conductivity of the composite halide electrolyte, worsen lithium-ion transport kinetics, and decrease discharge capacity and initial efficiency.
[0081] In some embodiments, the halide electrolyte particles comprise Li x M 1a M 2b X c The material, wherein the second non-lithium cation includes cations corresponding to elements M1 and M2, M1 includes one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy, M2 includes one or more of Si, Ge, Sn, Ti, Zr, and Hf, and X includes one or more of F, Cl, Br, and I, 1≤x≤3.2, 0≤a≤1, 0≤b≤1, 3≤c≤7, and 0.9≤a+b≤1.1.
[0082] For example, x can be any value or a range of values between 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.1, 3.15, 3.18, and 3.2.
[0083] For example, 'a' can be any value or a range of values between 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.92, 0.94, 0.96, 0.98, and 1.
[0084] For example, b can be any value or a range of values between 0, 0.05, 0.15, 0.25, 0.35, 0.45, 0.55, 0.65, 0.75, 0.85, 0.9, 0.93, 0.95, 0.97, and 1.
[0085] For example, c can be any value or a range of values between 3, 3.5, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, and 7.
[0086] The aforementioned halide electrolytes have a wide voltage window and exhibit good electrochemical stability at high voltages.
[0087] In some embodiments, the halide electrolyte particles include Li 2.4 Y 0.4 Zr 0.65 Cl 6.2 Li 2.5 La 0.5 Zr 0.5 Cl6, Li 2.4 La 0.43 Zr 0.5 Cl 6.1 One or more of them.
[0088] In some embodiments, the oxide comprises a first material and a second material, the first material comprising N0 1a1 O n1 The material Z1c1, the second material includes N... 2a2 O n2 The material Z2c2; wherein, the first non-lithium cation includes cations corresponding to elements N1 and N2, N1 and N2 each independently include one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, Dy, Si, Ge, Sn, Ti, Zr, and Hf, and Z1 and Z2 each independently include one or more of F, Cl, Br, and I; 0.5≤x1≤1, 0.5≤a1≤1, 1≤n1≤5, 0≤c1≤4, 0.5≤a2≤1, 1≤n2≤5, and 0≤c2≤4.
[0089] For example, x1 can be any value or a range of values between 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, and 1.
[0090] For example, a1 can be any value or a range of values between 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, and 1.
[0091] For example, n1 can be any value or a range of values between 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 4, and 5.
[0092] For example, c1 can be any value or a range of values between 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, and 4.
[0093] For example, a2 can be any value or a range of values between 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, and 1.
[0094] For example, n2 can be any value or a range of values between 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 4, and 5.
[0095] For example, c2 can be any value or a range of values between 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, and 4.
[0096] The oxide material of the ion-conducting-insulating composite layer is, as mentioned above, a mixture of at least lithium-containing oxyhalides and lithium-free oxyhalides. Both contain MO (transition metal-oxygen) bonds, which can reduce side reactions between Li-X and TM-X bonds and water, improving the humid air environment of the composite halide electrolyte. The lithium-containing oxyhalide first material has good ion-conducting properties, improving the capacity performance of the battery cell, and can capture O2 generated by the decomposition of the positive electrode active material in the positive electrode film layer through Li+ vacancies. 2 - It suppresses oxygen release and does not contain lithium oxyhalides. The second material has halogen ion vacancies that form composite defects with the Li+ vacancies of the first material. Through electron transfer, it can enhance the electron-ion coupling at the interface and improve the structural stability of the composite halide in the positive electrode. The battery cell has high charge and discharge capacity and first efficiency, as well as good cycle performance.
[0097] In some embodiments, the composite halide electrolyte satisfies: (σ1-σ2) / σ1 is 0.1 to 0.3; σ1 is the ionic conductivity of the composite halide electrolyte in an environment of 30°C, and σ2 is the ionic conductivity of the composite halide electrolyte after standing in an environment of -50°C for 12 hours.
[0098] For example, (σ1-σ2) / σ1 can be any value or a range of values between 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, and 0.3.
[0099] The ion change rate of composite halides in humid air environments is within the above range, and they have good stability. On the one hand, this can improve the overall stability of the positive electrode sheet and the cycle performance of the battery cell. On the other hand, it can reduce the stringent requirements for environmental humidity during battery assembly, reduce the construction cost of the workshop, and reduce the production cost.
[0100] In some implementations, σ2 is 0.9 mS / cm to 2.0 mS / cm, optionally 0.9 mS / cm to 1.3 mS / cm, optionally 0.95 mS / cm to 1.5 mS / cm, or optionally 1 mS / cm to 1.5 mS / cm.
[0101] For example, σ can be any value or a range of any values between 0.9 mS / cm, 0.95 mS / cm, 1 mS / cm, 1.05 mS / cm, 1.1 mS / cm, 1.15 mS / cm, 1.2 mS / cm, 1.25 mS / cm, 1.3 mS / cm, 1.35 mS / cm, 1.4 mS / cm, 1.45 mS / cm, 1.5 mS / cm, 1.55 mS / cm, 1.6 mS / cm, 1.65 mS / cm, 1.7 mS / cm, 1.75 mS / cm, 1.8 mS / cm, 1.85 mS / cm, 1.9 mS / cm, 1.95 mS / cm, and 2.0 mS / cm.
[0102] The composite halide electrolyte exhibits good ionic conductivity and stability after prolonged exposure to humid air.
[0103] In some implementations, σ1 is 0.7 mS / cm to 3 mS / cm, optionally 1.0 mS / cm to 2 mS / cm, or optionally 1.4 mS / cm to 2.0 mS / cm.
[0104] For example, σ1 can be any value or a range of any values between 0.7 mS / cm, 0.9 mS / cm, 1 mS / cm, 1.1 mS / cm, 1.2 mS / cm, 1.3 mS / cm, 1.4 mS / cm, 1.5 mS / cm, 1.6 mS / cm, 1.7 mS / cm, 1.8 mS / cm, 1.9 mS / cm, 2 mS / cm, 2.1 mS / cm, 2.2 mS / cm, 2.3 mS / cm, 2.4 mS / cm, 2.5 mS / cm, 2.6 mS / cm, 2.7 mS / cm, 2.8 mS / cm, 2.9 mS / cm, and 3 mS / cm.
[0105] Composite halide electrolytes with an ion-conducting-insulating composite layer on their surface not only have a small ion change rate in humid air environments, but also maintain good ion conductivity at 30°C, which is beneficial for improving discharge capacity and first-time efficiency. They can have good lithium-ion transport capabilities while improving stability in humid air environments, thus taking into account both the cycle performance and capacity performance of individual battery cells.
[0106] In some embodiments, the mass fraction of the composite halide electrolyte in the positive electrode film is 10% to 40%.
[0107] For example, the mass fraction of the composite halide electrolyte in the positive electrode film can be any value or a range of any values between 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, and 40%.
[0108] Within the above-mentioned range, the mass fraction of the composite halide electrolyte in the positive electrode film can balance the content of the positive electrode active material in the positive electrode sheet, thereby balancing the ionic conductivity of the positive electrode film and the energy density of the battery cell.
[0109] In some embodiments, the volume distribution particle size Dv50 of the composite halide electrolyte is 1 μm to 3 μm.
[0110] For example, the volume distribution particle size Dv50 of the complex halide electrolyte can be any value or a range of any values between 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, and 3 μm.
[0111] The test method for the volume distribution particle size Dv50 of the composite halide electrolyte is as follows: take 0.5g to 1g of composite electrolyte material sample, grind it initially, add it to a Venturi tube, disperse it at a pressure of 0.5bar to 2bar, and select the dry method mode of the Malvern laser particle size analyzer to test it. The particle size distribution curve and particle size value can then be obtained.
[0112] In some embodiments, the positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds.
[0113] The modified compound can be a doping modification and / or surface coating modification of the positive electrode active material particles, such as transition metal doping or carbon coating modification.
[0114] Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, lithium titanium oxides, and their respective modified compounds. Lithium transition metal oxides may include, but are not limited to, layered structures and spinel structures.
[0115] Examples of lithium phosphates may include, but are not limited to, lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and one or more of their respective modified compounds.
[0116] In some embodiments, the positive electrode active material may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, and LiNi 1 / 2 Mn 1 / 2 O2, LiMn2O4, Li 4 / 3 Ti 5 / 3 O4, LiNi 1 / 2 Mn 1 / 2 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.80 Co 0.15 Al 0.05 O2, LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3 One or more of S2.
[0117] In some embodiments, the positive electrode film layer further includes a positive electrode conductive agent, which may include, but is not limited to, one or more of conductive graphite (such as KS-6, SFG-6), VGCF, superconducting carbon, acetylene black, carbon black (such as SP), Ketjen black (such as ECP), carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown carbon fiber (VGCF).
[0118] In some embodiments, the positive electrode film layer further includes a positive electrode binder, which may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, water-soluble unsaturated resin SR-B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene-butadiene rubber (SBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), fluororubber, and acrylate rubber, or one or more of these.
[0119] The electrolyte is coated with an outer layer of inert hydrophobic material such as lithium salt (e.g., Al2O3), or the surface is treated with an F source to form an inert LiF layer. These methods of introducing an inert passivation layer often require complex processes such as ALD, and the thickness is difficult to control. Moreover, the ionic conductivity decreases significantly after coating, which inhibits lithium-ion transport kinetics.
[0120] The embodiments of this disclosure also provide a method for preparing a single battery cell, comprising:
[0121] A first halide electrolyte is provided, and the first halide electrolyte is oxidized to form an ion-conducting-insulating composite layer containing oxides on at least a portion of the surface of the first halide electrolyte, thereby preparing a composite halide electrolyte.
[0122] A positive electrode slurry is prepared by placing a composite halide electrolyte and a positive electrode active material in a solvent, and the positive electrode slurry is provided to form a positive electrode sheet on at least one side of the positive electrode current collector;
[0123] A battery cell is formed by assembling a positive electrode, a solid electrolyte layer, and a negative electrode.
[0124] The first halide electrolyte is an unoxidized electrolyte that, after oxidation, forms at least a portion of its surface with an ion-conducting-insulating composite layer containing oxides, forming a core-shell-like structure. The shell corresponds to the ion-conducting-insulating composite layer formed after oxidation, thus forming a composite halide electrolyte.
[0125] This method controls surface oxidation of the first halide electrolyte through heat treatment, enabling the construction of a controllable thickness ion-conducting-insulating composite layer containing oxides on the surface. While the composite halide electrolyte exhibits high bulk ion conductivity, the oxide material in the surface ion-conducting-insulating composite layer contains transition metal (TM)-O bonds, which reduces side reactions between Li-X, TM-X bonds, and water. This improves the electrolyte's wet air stability while maintaining good lithium-ion transport kinetics. Simultaneously, the surface ion-conducting-insulating composite layer suppresses oxygen release from the ternary cathode during cycling, thereby improving the cycle performance of the battery cells. This method is simple, controllable, and allows for thin-layer inert passivation, while also being low-cost.
[0126] The ion-conducting-insulating composite layer is formed on the surface of halide electrolyte particles. The halide electrolyte particles are the direct source of elements in the oxides; during oxidation, the atoms and ions on the surface of the halide electrolyte particles preferentially participate in the reaction. Therefore, the oxides in the ion-conducting-insulating composite layer are mainly formed by the combination of the second non-lithium cation on the surface of the halide electrolyte particles and oxygen. This results in the first non-lithium cation in the oxides being of the same type as the second non-lithium cation in the halide electrolyte particles.
[0127] In some embodiments, the oxidation treatment temperature is 150°C to 400°C.
[0128] For example, the oxidation treatment temperature can be any value or a range of any values between 150°C, 160°C, 170°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C.
[0129] In some embodiments, the oxidation treatment time is 0.5 h to 3 h.
[0130] For example, the oxidation treatment time can be any value or a range of any values between 0.5h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 2.9h, 2.95h, and 3h.
[0131] Oxidation treatments, such as increasing heat treatment time and temperature, can enhance the oxidation degree of the electrolyte surface, thereby controlling the thickness of the ion-conducting-insulating composite layer. A thicker ion-conducting-insulating composite layer improves water stability and electrochemical stability, and also enhances the chemical compatibility between the cathode material and the electrolyte.
[0132] In some embodiments, the gas flow rate for oxidation treatment is 50 mL / min to 100 mL / min.
[0133] For example, the gas flow rate for oxidation treatment can be any value or a range of any values between 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, 75 mL / min, 80 mL / min, 85 mL / min, 90 mL / min, 91 mL / min, 92 mL / min, 93 mL / min, 94 mL / min, 95 mL / min, and 100 mL / min.
[0134] In some embodiments, the atmosphere for the oxidation treatment includes 0.1% to 2% O2 by volume and / or 98% to 99.9% inert gas by volume.
[0135] For example, the volume fraction of O2 can be any value or a range of any values between 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, and 2%.
[0136] For example, the volume fraction of the inert gas can be any value or a range of any values between 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, and 99.9%.
[0137] [Solid electrolyte layer]
[0138] In some embodiments, the battery cell further includes a solid electrolyte layer, wherein the solid electrolyte includes one or more of sulfide electrolytes, halide electrolytes, and oxide solid electrolyte materials.
[0139] In some embodiments, the sulfide electrolyte may include, but is not limited to, one or more of the following sulfide solid electrolyte materials: silver-germanium sulfide type, LGPS type, lithium sulfide-phosphorus pentasulfide complex type.
[0140] Optionally, the sulfide solid electrolyte material of the silver-germanium sulfide type may include Li 6±s P 1-j A j S 5±s- t B t X 1±sof material, 0≤j<1, 0≤t<1, 0≤s<1, A includes one or more elements selected from Ge, Si, Sn and Sb, B includes one or more elements selected from O, Se and Te, X includes one or more elements selected from Cl, Br, I and F.
[0141] Optionally, the LGPS-type sulfide solid electrolyte material may include a chemical formula of Li 10±δ5 Ge 1-g G g P 2-q Q q S 12- w GgSw of material, 0≤δ5<1, 0≤g≤1, 0≤q≤2, 0≤w<1, G includes one or two elements selected from Si and Sn, Q includes Sb, W includes one or more elements selected from O, Se, Te, Cl, Br, I and F.
[0142] Optionally, the lithium sulfide-phosphorus pentasulfide complex-type sulfide solid electrolyte material may include a chemical formula of (100-u-v)Li2S·uP2S5·vMmNn m N n of material, 0<u<100, 0≤v<100, 0≤u+v<100, 0≤m<4, 0≤n<6, M includes one or more elements selected from Li, B, Ge, Si, Sn and Sb, N includes one or more elements selected from S, Se, Te, O, Cl, Br, I and F.
[0143] In some embodiments, by way of example, the sulfide solid electrolyte material may include one or more of Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 , Li3PS4, Li7P3S 11 , Li2S-GeS2, Li2S-P2S5, Li2S-SiS 2、 and Li2S-MeS2-P2S5 (Me=Si, Ge, Sn, Al, etc.).
[0144] In some embodiments, the solid electrolyte layer includes sulfide electrolyte particles. The sulfide electrolyte particles include Li 7-a PS5Cl a , Li 10 GeP2S 12 , and Li3PS4, one or more thereof.
[0145] In some embodiments, the halide electrolyte may include one or more of Li3YCl6, Li3YBr6, Li3ErCl6, Li3InCl6, and Li3InBr6.
[0146] In some embodiments, the oxide solid electrolyte material may include one or more of the following: perovskite structure oxide solid electrolyte material, garnet structure oxide solid electrolyte material, NASICON structure oxide solid electrolyte material, and LISICON structure oxide solid electrolyte material.
[0147] In some embodiments, the electrolyte layer may further include an adhesive. Optionally, the adhesive may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), styrene-butadiene rubber (SBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, butadiene rubber (BR), ethyl cellulose, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), fluororubber, and acrylate rubber.
[0148] [Negative electrode plate]
[0149] In some embodiments, the battery cell further includes a negative electrode sheet, which may include one or more of lithium and lithium alloys.
[0150] Optionally, the mass fraction of lithium in the lithium alloy can be above 90%.
[0151] Optionally, other elements in the lithium alloy may include, but are not limited to, one or more of In, Mg, Al, Cu, Zn, Sn, Ag, Au, Ga, Pt, and Fe.
[0152] Alternatively, the lithium alloy may include, but is not limited to, Li-In alloy, Li-Mg alloy, Li-Al alloy, Li-Cu alloy, Li-Zn alloy, Li-Fe alloy, etc.
[0153] In some embodiments, the negative electrode sheet may further include a negative electrode binder, which may include, but is not limited to, one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-B, polyacrylic acid, polymethacrylic acid, sodium polyacrylate, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.
[0154] In some embodiments, the negative electrode sheet may include a negative electrode conductive agent, which may include, but is not limited to, one or more of conductive graphite (such as KS-6, SFG-6), superconducting carbon, acetylene black, carbon black (such as SP), Ketjen black (such as ECP), carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).
[0155] In some implementations, the negative electrode current collector can be a metal foil, a three-dimensional porous current collector, or a composite current collector.
[0156] Examples of metal foils include copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil. Examples of three-dimensional porous current collectors include copper mesh, nickel mesh, aluminum mesh, copper foam, nickel foam, and aluminum foam. Composite current collectors may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As examples, the metal material may include, but is not limited to, one or more of copper, copper alloys, aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As examples, the polymer material base layer may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, and polyethylene.
[0157] Example
[0158] The following embodiments describe the contents disclosed in this disclosure in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0159] Example 1
[0160] 1. Preparation of positive electrode sheet
[0161] LiCl, YCl3, and ZrCl4 were added to a ball mill jar in stoichiometric ratio, with a fixed ball-to-material ratio of 30:1. The jar was milled at 600 rpm for 16 hours, with a rotation-to-plane ratio of 1:2, to obtain the first halide electrolyte, LiCl. 2.4 Y 0.4 Zr 0.65 Cl 6.2 Take the above Li 2.4 Y 0.4 Zr 0.65 Cl 6.2 The mixture was placed in a crucible and transferred to a tube furnace. The atmosphere was replaced twice with 1% O2 + 99% Ar. The mixture was calcined at 300°C for 0.5 h at a heating rate of 5°C / min. After cooling, a composite halide electrolyte with an ion-conducting and insulating composite layer containing oxides was obtained on at least part of the surface.
[0162] VGCF, the aforementioned composite halide electrolyte, and the cathode material (LiNi) were used. 0.83 Mn 0.05 Co 0.12 O2) is mixed in a mass ratio of 1:24:80 and ground for 30 minutes to form a composite positive electrode powder. The composite positive electrode powder is then coated on the surface of the positive current collector aluminum foil to obtain the positive electrode sheet.
[0163] 2. Preparation of negative electrode sheet
[0164] Indium foil and composite copper-lithium foil, with the lithium side facing the solid electrolyte layer.
[0165] 3. Solid electrolyte layer
[0166] Sulfide electrolyte Li6PS5Cl.
[0167] 5. Battery manufacturing
[0168] First, a sulfide electrolyte Li6PS5Cl is added and weakly pressed into a sheet (2MPa) to serve as a solid electrolyte layer. Then, an indium sheet and a composite copper-lithium sheet (lithium side facing the electrolyte layer) are added sequentially to one side of the solid electrolyte layer. Finally, a positive electrode sheet is added to the other side of the solid electrolyte layer and the pressure is increased to 40MPa and held for 4 minutes to obtain a single battery cell.
[0169] Examples 2-8
[0170] Solid-state batteries were prepared using a method similar to that in Example 1. The difference from Example 1 is that the preparation method of the composite halide electrolyte is different, and the varying parameters are shown in Table 1.
[0171] Comparative Example 1
[0172] Solid-state batteries were prepared using a method similar to that in Example 1. The difference from Example 1 is that the preparation method of the positive electrode sheet is different. That is, after obtaining the first halide electrolyte, there is no oxidation treatment, and it is directly used to make the positive electrode sheet.
[0173] Preparation of the positive electrode: LiCl, YCl3, and ZrCl4 were added to a ball mill jar in stoichiometric ratio, with a fixed ball-to-material ratio of 30:1. The mixture was ball-milled at 600 rpm for 16 hours with a rotation-to-plane ratio of 1:2 to obtain the first halide electrolyte Li. 2.4 Y 0.4 Zr 0.65 Cl 6.2 VGCF, the aforementioned first halide electrolyte, and the cathode material (LiNi) are added. 0.83 Mn 0.05 Co 0.12 O2) is mixed in a mass ratio of 1:24:80 and ground for 30 minutes to form a composite positive electrode powder. The composite positive electrode powder is then coated on the surface of the positive current collector aluminum foil to obtain the positive electrode sheet.
[0174] Performance testing
[0175] 1. Thickness of the ion-conducting-insulating composite layer: The thickness of the ion-conducting-insulating composite layer is characterized by the Ar etching time and etching energy of XPS.
[0176] like Figure 3 As shown, the thickness of the surface ion-conducting-insulating composite layer of Example 1 was quantitatively characterized by O1s energy dispersive spectroscopy. Example 1 exhibited typical transition metal (M)-oxygen (O) bonding at 530–531 eV, while Comparative Example 1 only showed the binding peak of exogenous carbon contamination and O. This characteristic bonding (MO) was not detected in Example 1 after 1 min of Ar etching. Based on the XPS etching energy, the thickness of the ion-conducting-insulating composite layer containing MO bonds can be determined to be 5 nm.
[0177] 2. Test method for σ1: Press 120mg to 150mg of solid electrolyte powder into a 40MPa mold and perform impedance testing. Set the test frequency range to 0.1Hz-1MHz and the AC voltage amplitude to 100mV before starting the test. Calculate the ionic conductivity based on the impedance value and the layer thickness.
[0178] The test method for σ² was as follows: The composite halide electrolyte was exposed to a -50℃ dew point environment for 12 hours. 1g of powder was spread evenly in a 10cm diameter mortar, and then pressed into a tablet in a 40MPa mold. Impedance testing was performed. The test frequency range was set to 0.1Hz-1MHz, and the AC voltage amplitude was 100mV before the test began. The ionic conductivity was calculated based on the impedance value and the tablet thickness. The performance test results are shown in Table 2.
[0179] 3. Electrical Performance Test: Under a constant temperature environment of 25℃, the battery was left to stand for 5 minutes, then discharged at 0.1C to 2.0V, left to stand for 5 minutes, then charged at 0.1C to 4.3V, and then charged at a constant voltage of 4.3V until the current ≤0.05mA. After a 5-minute stand, the charging capacity was recorded as D0. Then, the battery was discharged at 0.1C to 2.0V, and the discharge capacity at this point was recorded as the initial specific capacity, denoted as C0. The initial capacity is calculated as C0 / D0. The above steps were repeated for the same battery, and the discharge capacity Cn was recorded after the 50th cycle. The battery capacity retention rate after each cycle is calculated as P = (Cn / C0) × 100%. The performance test results are shown in Table 3.
[0180] Table 1
[0181]
[0182]
[0183] In Table 1, the first halide electrolyte is oxidized at high temperature to form an ion-conducting-insulating composite layer on its surface. Since the first halide electrolyte has many elements, the elements in the halide electrolyte will undergo complex chemical reactions with oxygen, which may form oxides with different valence states. Therefore, it is difficult to determine the specific chemical formula of the oxides in the final ion-conducting-insulating composite layer.
[0184] Table 2
[0185]
[0186]
[0187] Table 3
[0188]
[0189] As shown in Tables 1-3, the embodiments of this disclosure control surface oxidation by heat-treating the first halide electrolyte, and constructing an ion-conducting-insulating composite layer containing oxides with controllable thickness on the surface. While the composite halide electrolyte has high bulk ion conductivity, the oxide material in the surface ion-conducting-insulating composite layer contains transition metal (TM)-O bonds, which reduces the side reactions of Li-X, TM-X bonds and water. Thus, the wet air stability of the electrolyte can be improved on the basis of good lithium-ion transport kinetics, thereby improving the cycle performance of the battery cell.
[0190] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present disclosure, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.
Claims
1. A battery cell, characterized in that, The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film includes a composite halide electrolyte and a positive electrode active material. The composite halide electrolyte includes halide electrolyte particles and an ion-conducting-insulating composite layer. The ion-conducting-insulating composite layer covers at least a portion of the surface of the halide electrolyte particles. The ion-conducting-insulating composite layer includes an oxide, and the oxide includes a first non-lithium cation. The halide electrolyte particles include a second non-lithium cation, and the first non-lithium cation is selected from at least one of the second non-lithium cations.
2. The battery cell according to claim 1, characterized in that, The first non-lithium cation is of the same type as the second non-lithium cation.
3. The battery cell according to claim 1, characterized in that, The thickness of the ion-conducting-insulating composite layer is 5 nm to 20 nm.
4. The battery cell according to any one of claims 1 to 3, characterized in that, The halide electrolyte particles include those with the molecular formula Li x M 1a M 2b X c Materials, Wherein, the second non-lithium cation includes cations corresponding to elements M1 and M2. M1 includes one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy. M2 includes one or more of Si, Ge, Sn, Ti, Zr, and Hf. X includes one or more of F, Cl, Br, and I. 1≤x≤3.2, 0≤a≤1, 0≤b≤1, 3≤c≤7, and 0.9≤a+b≤1.
1.
5. The battery cell according to any one of claims 1 to 4, characterized in that, The halide electrolyte particles include Li 2.4 Y 0.4 Zr 0.65 Cl 6.2 Li 2.5 La 0.5 Zr 0.5 Cl6, Li 2.4 La 0.43 Zr 0.5 Cl 6.1 One or more of them.
6. The battery cell according to any one of claims 1 to 5, characterized in that, The oxide comprises a first material and a second material, wherein the first material comprises Li₂. x1 N 1a1 O n1 The material Z1c1, the second material comprising N... 2a2 O n2 Z2c2 materials; The first non-lithium cation includes cations corresponding to elements N1 and N2. N1 and N2 each independently include one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, Dy, Si, Ge, Sn, Ti, Zr, and Hf. Z1 and Z2 each independently include one or more of F, Cl, Br, and I. 0.5≤x1≤1, 0.5≤a1≤1, 1≤n1≤5, 0≤c1≤4, 0.5≤a2≤1, 1≤n2≤5, and 0≤c2≤4.
7. The battery cell according to any one of claims 1 to 6, characterized in that, The composite halide electrolyte satisfies the following condition: (σ1-σ2) / σ1 is 0.1 to 0.
3. σ1 is the ionic conductivity of the composite halide electrolyte at 30°C, and σ2 is the ionic conductivity of the composite halide electrolyte after standing at -50°C for 12 hours.
8. The battery cell according to claim 7, characterized in that, The σ2 is 0.9 mS / cm to 1.3 mS / cm.
9. The battery cell according to claim 7 or 8, characterized in that, The σ1 is 0.7 mS / cm to 3 mS / cm.
10. The battery cell according to any one of claims 1 to 9, characterized in that, The composite halide electrolyte must satisfy at least one of the following characteristics: (1) The mass fraction of the composite halide electrolyte in the positive electrode film is 10% to 40%; (2) The volume distribution particle size Dv50 of the composite halide electrolyte is 1μm to 3μm.
11. The battery cell according to any one of claims 1 to 10, characterized in that, The positive electrode active material includes one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds.
12. The battery cell according to any one of claims 1 to 11, characterized in that, The battery cell further includes a solid electrolyte layer, which comprises sulfide electrolyte particles, and the sulfide electrolyte particles comprise Li 7- a PS5Cl a Li 10 GeP2S 12 One or more of Li3PS4.
13. A battery device, characterized in that, It includes multiple battery cells as described in any one of claims 1 to 12.
14. An electrical appliance, characterized in that, It includes multiple battery cells as described in any one of claims 1 to 12 or battery devices as described in claim 13.
15. A method for preparing a single battery cell, characterized in that, include: A first halide electrolyte is provided, and the first halide electrolyte is oxidized to form an ion-conducting-insulating composite layer containing oxides on at least a portion of the surface of the first halide electrolyte, thereby preparing a composite halide electrolyte. The composite halide electrolyte and the positive electrode active material are placed in a solvent to prepare a positive electrode slurry, and the positive electrode slurry is provided to form a positive electrode sheet on at least one side of the positive electrode current collector; The positive electrode, solid electrolyte layer and negative electrode are assembled to form a battery cell.
16. The method for preparing a single battery cell according to claim 15, characterized in that, The oxidation treatment must satisfy at least one of the following characteristics: (1) The oxidation treatment temperature is 150℃~400℃; (2) The oxidation treatment time is 0.5h to 3h; (3) The gas flow rate for the oxidation treatment is 50 mL / min to 100 mL / min; (4) The atmosphere of the oxidation treatment includes 0.1% to 2% O2 by volume and / or 98% to 99.9% inert gas by volume.